2010
DOI: 10.2478/s11658-010-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrin receptors play a role in the internalin B-dependent entry of Listeria monocytogenes into host cells

Abstract: Abstract:Listeria monocytogenes enters non-phagocytic cells by binding its surface proteins inlA (internalin) and inlB to the host's E-cadherin and Met, respectively. The two internalins play either separate or cooperative roles in the colonization of infected tissues. Here, we studied bacterial uptake into HeLa cells using an L. monocytogenes mutant strain (ΔinlA) carrying a deletion in the gene coding for inlA. The ΔinlA mutant strain showed the capability to invade HeLa cells. The monoclonal anti-β 3 -and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The one exception is the rapid uptake of L. monocytogenes, a function that is prominent in CD8 1 DCs but not in CD8 À DCs [5]. This enhanced uptake corresponds with CD103 expression and it is tempting to speculate that CD103 as a b integrin might be aiding internalin B-mediated engulfment [22]. It is not clear whether uptake of other bacterial pathogens by CD8 1 DCs will be influenced in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…The one exception is the rapid uptake of L. monocytogenes, a function that is prominent in CD8 1 DCs but not in CD8 À DCs [5]. This enhanced uptake corresponds with CD103 expression and it is tempting to speculate that CD103 as a b integrin might be aiding internalin B-mediated engulfment [22]. It is not clear whether uptake of other bacterial pathogens by CD8 1 DCs will be influenced in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Rab5c, a protein that interacts with regulatory and catalytic subunits of type IA PI 3-kinase, could promote Listeria entry by controlling the host endocytic machinery (14,85). ARNO, an activator of Arf GTPases that binds directly to the PI 3-kinase product PI(3,4,5)P 3 , might help maintain proper levels of integrins, a class of receptor recently found to enhance InlB-mediated entry, in the plasma membrane (2). The serine/threonine kinase PKC-could promote Listeria internalization by controlling the actin cytoskeleton and/or the delivery of membrane through exocytosis (7,53,73).…”
Section: Discussionmentioning
confidence: 99%
“…P130Cas interacts with FAK through its SH3 domain and is then phosphorylated by Src, leading to recruitment of Crk, and enters the Rac→PAK→MAPK→JNK pathway through Dock1 (path 13) [9]. α-actin links tails of integrins and binds to zyxin, then also enter the Rac→ PAK → MAPK→JNK pathway (path 14) [13]. Previous studies indicated that Src protein expression and activity increased significantly in cells which had strong proliferation activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…In paths 5-13, FAK has many phosphorylation sites and combines with numerous intracellular signaling molecules including Src, PI3K (phosphoinositide 3-kinase), RhoGAP, RhoGEF, and p130CAS (Crk-associated substrate), then activates their downstream signaling pathways, such as mitogen-activated protein kinase (MAPK), c-Jun NH2-terminal kinase (JNK), and p21-activated kinase (PAK) signaling pathway [9,[11][12]. α-actinin links tails of integrins to actin fibrils, and also binds to several cytoplasmic molecules including vinculin, zyxin, and ERK1/2, forming path 14 [13]. In addition, CD47 associates with integrin heterodimer to form a protein complex; the complex stimulates Gs-mediated upregulation of the cAMP cascade through adenyl cyclase (AC), resulting in nuclear translocation of the catalytic subunit of protein kinase-A (PKA), and then enters into PKA→GSK3 and PKA→ERK cascade forming paths 15-16 [14].…”
Section: Introductionmentioning
confidence: 99%